The influence of spelling-checkers on students' ability to generate repairs of spelling errors / Hazelynn Rimbar - Rimbar, Hazelynn (2013)
Recent studies show that spell-checkers help reduces students’ surface error in writing by flagging spelling errors and giving correct spelling suggestions. However, are the error corrections provided by spelling checkers internalised by students? This study investigated whether the presence of spelling-checkers influenced students’ abilities to repair spelling errors. A quasi-experimental two groups study was conducted on 30 Form 1 students, one with spelling-checkers, and one without. The students were given dictations which contained target words. The checker helped the students revise their spelling. However, after the use of spelling checkers, students still made the same errors in their spelling. The findings suggest that spell-checkers have very little influence on students’ abilities to repair spelling errors.